MiR-181b-5p, miR-195-5p and miR-301a-3p are related with treatment resistance in schizophrenia. (30th November 2016) - Alacam, Huseyin; Akgun, Sakir; Akca, Hakan; Ozturk, Onder; Kabukcu, Burge Basay; Herken, Hasan
Abstract: The aim of the study was to determine the differences between expression levels of certain miRNAs, as their association with schizophrenia has been well presented in the literature, and to investigate their relation to treatment resistance in schizophrenic patients. Three groups were formed: 1) treatment-resistant group, 2) treatment responsive group and 3) healthy control group. Expression levels of miRNAs from peripheric blood samples were determined by real-time quantitative reverse transcription polymerase chain reaction (qRT-PCR). We investigated the roles of 29 schizophrenia-related miRNAs in schizophrenia treatment and their potentials to be considered as indicators. Among these miRNAs, only miR-181b-5p, miR-195-5p and miR-301a-3p expressions were found to be significantly different between the treatment-resistant group and the group responding well to the treatment. miRNAs may cause resistance by silencing the receptor genes of the drugs used for schizophrenia treatment. miR-181b-5p, miR-195-5p and miR-301a-3p may be candidate indicators that can be used to reveal resistance against schizophrenia treatment. Highlights: The study is important to understand the treatment resistance in schizophrenia. The first study shows the relationship between miRNAs and schizophrenia treatment. miR-181b-5p, miR-195-5p and miR-301a-3p may be used to reveal resistance.